O movimento dialógico de escrever: os gêneros do discurso como o lócus específico de manifestação da linguagem - ANDRADE, Maria Jandira de (2019)
Study about the production of texts at school, which has started with the following research problem: How have 5th grade students from UEB Agostinho Vasconcelos interacted with writing? What methodological possibilities can guide the production of texts at school, in order to consider the dialogical movement of the genres of discourse? The general objective was to understand the writing process in a dialogical perspective, seeking to develop methodological possibilities in the production of texts considering the genres of discourse. In order to do so, the following specific objectives were listed: to analyze the theoretical-methodological conceptions that guide the writing process and its implications on the formation of students as producers of texts; to develop an intervention in the process of writing in the 5th grade of Elementary School from UEB Agostinho Vasconcelos aiming at the formation of producers of texts, based on the discourse genres, having as presupposition the dialogical conception of language and, finally, to produce a notebook with methodological propositions aiming to guide the work with the production of texts at school. The action research methodology was chosen and, as data generation tools, participant observation, semi-structured interview and the children's notebook were used. The participants of the research were the teacher and the students of the 5th grade of Elementary School, and later, the researcher too. As a way of understanding the object of study, three thematic nuclei were organized: the conception of language, by subsidizing the work with writing in the classroom; the genres of discourse, by their vital correlation with the spheres or fields of human activity; and the production of texts as a dialogic practice because it makes sense for those who learn. As a theoretical reference, we have selected studies by Bakhtin (2016), Volochinov (2017) and Leontiev (1988), who point out in their theories relevant aspects of language as human interaction and as dialogical practice. We had also chased to refer authors who study the production of texts such as Jolibert (1994a, 1994b), Jolibert and Jacob (2006) Jolibert and Sraïk (2008), Smolka (2012, 2017), Goulart (2011) , Geraldi (2015), among others. As the product of the research, a Notebook with methodological propositions was elaborated, in order to guide the work with written production at school. The findings reveal that children need to be guided in the process of producing texts at school and the methodological path should make sense to them. So that, it must be based on the genres of discourse, and the immersion in these principles needs to work in a dialogical movement.